Analysis of the Behavior of Breastfeeding Mothers in Providing Exclusive Breastfeeding during the Covid 19 Pandemic in Surabaya (mix method) - Nur Masruroh; Lailatul Khusnul Rizki; Nadia Ayu Ashari; Irma Irma; Dzikriatul Laili (JURNAL KEBIDANAN, 2022)
The benefits of exclusive breastfeeding include increasing the baby's immune system, especially during the current Covid-19 pandemic. The purpose of this study was to determine the behavior and self-efficacy of breastfeeding mothers in providing exclusive breastfeeding and to determine the supporting and inhibiting factors in providing exclusive breastfeeding. The research method used is a mix method with a concurrent embedded strategy. The first stage is carried out with a quantitative method to determine the behavior and self-efficacy of breastfeeding mothers during the Covid-19 pandemic. The second stage is a qualitative method to determine the supporting factors, barriers to breastfeeding practices during the Covid-19 Pandemic. The population and samples in this study were breastfeeding mothers, midwives and breast milk counselors who were taken purposively as samples. The results of the study on knowledge that the p value of 0.001 (0.05) means that knowledge affects the behavior of mothers in giving exclusive breastfeeding. On the attitude of the analysis results obtained p value of 0.005 (0.05) which means that attitudes affect the behavior of mothers in exclusive breastfeeding. Then from the breastfeeding pattern, the results of the p value analysis were 0.001 (0.05), which means that the breastfeeding pattern affects the mother's behavior in giving exclusive breastfeeding. At the qualitative stage, it was found that the supporting factors for exclusive breastfeeding include the support of family and health workers, high knowledge and ease of accessing information. While the inhibiting factors are wrong perceptions about breastfeeding, there is no intention and inappropriate cultural practices about breastfeeding.